Dekreasi dan Atensi dalam Pemikiran Simone Weil: Reimajinasi Pelayanan Pastoral di Era Pandemi - Jessica Novia Layantara (Veritas : Jurnal Teologi dan Pelayanan, 2022)
This paper proposes a model of pastoral care in the pandemic era which is inspired by the concepts of decreation and attention in Simone Weil’s thinking. Decreation and attention are two important concepts in Weil's theological thought. Decreation in Weil's thought can be interpreted as denial of oneself so that the other can be revealed. The concept of decreation is inspired by God's act of withdrawal, which He did so that all creation could exist. Decreation manifests in attention, by emptying oneself, and being ready to be fully open to the disclosure of the other. Using Weil’s two concepts, this paper proposes “decreational ministry.” In this model, the church is no longer focused on pastoral ministries that are “creating” forms of service that attract many congregations to come to church, but instead focuses on placing other people or the congregation as the center of pastoral care. Decreational ministry thus has three characteristics: (1) space-giving, (2) friendly, (3) “empty” and “silent.”